A Study On Association Between Respiratory Tract Infection And Serum 25(Oh) Vitamin D3 Level In Children Of A Tertiary Care Hospital - Kumari, Nikki; Kumar, Rajesh; Ansarri, Athar; Singh, Binod Kumar (International Journal of Health and Clinical Research, 2021)
Respiratory tract infections (RTIs) are common worldwide and are responsible for significant morbidity and mortality. The most common causal agents are the bacterium Streptococcus pneumonia and influenza-virus. Aims and Objectives: To evaluate the level of serum 25(OH) Vitamin D3 in respiratory tract infection (both upper and lower) in children. Materials and Methods: A Case control study of total 105 cases of age group 2 months to 12 years from both indoor and OPD patients of Department of Pediatric Medicine, Nalanda Medical College and Hospital, Patna Bihar, were taken as cases who were suffering from respiratory tract infection and 86 disease free age and sex matched children were taken as control. Results: This study included total 196 children of age group 2 months to 12 years. 105 children who were suffering from respiratory tract infection were taken as cases and 86 disease free age and sex matched children were taken as controls. The mean age of cases was 40.88±37.57 months and that of control was 37.66±35.25. Maximum population were in vitamin D insufficient state both in case and control. Conclusion: To conclude supplementation of vitamin D may be useful in prevention of RTIs, specially the LRTI group and to decrease the number of PICU admission. However more studies are needed to be performed in this field to assess further correlation with frequency, severity and the types of RTIs.